2023
DOI: 10.1038/s41598-023-46935-x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of “My Jump app” to assess vertical jump performance: a meta-analytic review

Cebrail Gençoğlu,
Süleyman Ulupınar,
Serhat Özbay
et al.

Abstract: This systematic review and meta-analysis aims to investigate the validity and reliability of the My Jump smartphone application in measuring vertical jump height, specifically using flight-time-based measures. To identify potential studies for inclusion, a comprehensive search strategy was employed in PubMed, Web of Science, Scopus, and EBSCO host databases. Validity was assessed in two ways: (1) mean and standard deviations of My Jump measurements were compared to criterion methods to assess the agreement of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
5
0
1
Order By: Relevance
“…Previous studies have also assessed the validity of using My Jump for determing the MH during vertical jumps [2,3,6,9,[12][13][14][15][16]24,27]. Considering the comparison of this app with the force platform, Balsalobre-Fernandez et al [2], Carlos-Vivas et al [6], Driller et al [14] and Stanton et al [15] reported very close MH results and an almost perfect agreement (ICC greater than 0.970) between both methods, recommending the My Jump app as a valid tool for evaluating the CMJ height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also assessed the validity of using My Jump for determing the MH during vertical jumps [2,3,6,9,[12][13][14][15][16]24,27]. Considering the comparison of this app with the force platform, Balsalobre-Fernandez et al [2], Carlos-Vivas et al [6], Driller et al [14] and Stanton et al [15] reported very close MH results and an almost perfect agreement (ICC greater than 0.970) between both methods, recommending the My Jump app as a valid tool for evaluating the CMJ height.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the jump height obtained from the flight time is made easier by the installation of the My Jump app on a smartphone, which is much cheaper than laboratory devices [12,13]. Importantly, the My Jump app was validated by comparing this application with the force platform as a criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Both cameras [42,43] and microphones [44] have been used to characterize time of flight, which can be used to estimate jump height, similar to one of the applications described in this tutorial.…”
Section: Other Sensorsmentioning
confidence: 99%
“…Sin embargo, un estudio reciente mostró una buena concordancia entre calificadores entrenados y no entrenados para la evaluación de la altura del salto, lo que indica que la aplicación de vídeo tiene una buena fiabilidad entre calificadores (Pueo, Jimenez-Olmedo, Penichet-Tomas, & Bernal-Soriano, 2018). Otra desventaja, es el riesgo de que el sujeto prolongue de forma artificial el tiempo de vuelo debido a la flexión (dorsiflexión) de rodilla y tobillo justo antes del aterrizaje, lo que le daría un mayor tiempo de vuelo y por consiguiente una mayor altura del salto alcanzada (Gençoğlu, et al, 2023).…”
Section: Evaluación Del Salto Verticalunclassified